Predicting academic achievement in music in secondary schools: The role of personality and self-theories of musicality - Lin, Hsin-Rui; Kopiez, Reinhard; Muellensiefen, Daniel; Hasselhorn, Johannes (Psychology of Music, 2022)
Recent meta-analyses have confirmed the significance of three personality traits of the Five-Factor Model (FFM) in predicting academic achievement, namely, conscientiousness, emotional stability (neuroticism), and openness. However, there is little agreement on which FFM traits are relevant in predicting academic achievement in music. The underlying mechanisms for the observed correlations between personality traits and academic achievement are also unclear. Thus, by including self-theories as mediator variables, we examine the relationships between personality traits, academic achievement in music and their underlying mechanisms. We analyzed longitudinal data collected from secondary school students (N = 564, Mage = 11.98) in Germany and the United Kingdom in 2017 and 2018. A series of path models were used to examine the effect of personality traits and self-theories on academic achievement in music and overall achievement, while controlling for previous achievement. Conscientiousness and agreeableness emerged as best predictors of the development of overall performance and achievement in music, respectively. Subjective theories about one’s own musicality (e.g., musical self-theories) affect academic achievement in music even when personality traits and previous achievements are accounted for. This study demonstrates that personality traits contribute to the development of musical self-theories that in turn affect the growth of academic achievement in music.
CRIS-Team Scopus Importer:2023-03-21
Keywords: academic achievement in music; agreeableness; conscientiousness; development; longitudinal study; self-theories of musicality